Productivity effects of trade in natural resources: Comparison with mechanisms of technological specialisation - Zuzanna Zarach; Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2022)
This paper compares two alternative growth paths, assessing the effects on productivity of specialisation in natural resources (NR) and in technologically advanced products. The empirical analysis exploits product-level export data for 109 developing and 51 developed economies over the period 1996-2018. We document two distinct types of specialisation, based on exports either of natural resources or of technological products, and compare their role in productivity growth by GMM estimation of a conditional convergence model. In general, reliance on natural resource exports slows growth, but we find that the type of resources exported is important: fuel exports hamper growth while specialisation in metals enhances the catch-up in productivity. Technological specialisation, especially in products typical of the Fourth Industrial Revolution, reinforces productivity growth but does not affect the relationship between resources and productivity growth.
Keywords: O13; O47; O3; Q32; 330; natural resources; technological specialisation; productivity growth; convergence